Comparative Chloroplast Genomics at Low Taxonomic Levels: A Case Study Using Amphilophium (Bignonieae, Bignoniaceae) - Thode, Verônica A.; Lohmann, Lúcia G. (Frontiers in Plant Science, 2019)
Chloroplast (cp) genome organization, gene order, and content have long been considered conserved among land plants. Despite that, the generation of thousands of complete plastomes through next-generation sequencing (NGS) has challenged their conserved nature. In this study, we analyze 11 new complete plastomes of Amphilophium (Bignonieae, Bignoniaceae), a diverse genus of Neotropical lianas, and that of Anemopaegma prostratum. We explored the structure and content of the assembled plastomes and performed comparative analyses within Amphilophium and with other plastomes available for Bignoniaceae. The overall gene content and orientation of plastomes is similar in all species studied. Plastomes are not conserved among Amphilophium, showing significant differences in length (155,262–164,786 bp), number of genes duplicated in the IRs (eight, 18, or 19), and location of the SC/IR boundaries (i.e., LSC/IRa junction between rps19 and rpl2 genes, within petD, or within petB). Length differences reflect expansions of the IRs and contractions of the LSC regions. The plastome of A. prostratum is 168,172 bp and includes 19 duplicated genes, and LSC/IRa boundary located within the petB gene. Amphilophium plastomes show high nucleotide diversity, with many hypervariable regions, and 16 genes with signatures of positive selection. Multiple SSRs and repeat regions were identified for Amphilophium and Anemopaegma prostratum. The differences in structure detected within Amphilophium plastomes in terms of LSC/IR and IR/SSC boundaries, number of duplicated genes, and genome sizes are mostly shared between taxa that belong to the same clade. Our results bring new insights into the evolution of plastomes at low taxonomic levels.